Legal Control of the Private Military Corporation - Sheehy, B. author. aut Link
XII, 252 p.
Keywords: Private military organizations are a new and important feature of the international landscape. They offer control of potential massive violence to the highest bidder with very limited accountability. This book offers critical insights into both the phenomenon and the challenges of and potential for regulation.